Antibiotic Resistance in Escherichia coli and Staphylococcus aureus from Retail Chicken Meat in Surabaya, Indonesia - Annisa Aulia Maghfirani Sudarmadi; Subur Prajitno; Agung Dwi Wahyu Widodo (Biomolecular and Health Science Journal, 2020)
Introduction: Antimicrobial resistance is becoming a problem in public health. Zoonotic food-borne bacteria is infectious agent that can be transferred from animal to human through the food-producing animal we consume. Nowadays, antibiotic used for human and animal is not only to cure infection but also to aim animal’s growth promotion. It is known as non therapeutic antimicrobial agent (NTA) leading to antibiotic resistance. The third generation cephalosporins, cefotaxime, and also cefoxitin are included as important antibiotic for human. This study aims to identify the presence of cefotaxime-resistant Escherichia coli and cefoxitin-resistant Staphylococcus aureus isolated from chicken meat of both traditional and modern market in Surabaya.Methods: This is descriptive post test only experimental research. We used 8 samples of chicken meat from 4 different market using purposive sampling technique. We cultured Escherichia coli and Staphylococcus aureus from the chicken meat. Sensitivity test was done using Kirby-bauer disk-diffusion method.Results: All chicken meat sample bought from traditional market in Surabaya are contaminated by cefotaxime-sensitive Escherichia coli (n=4/4) while chicken meat sample bought from modern market are not contaminated by Escherichia coli (n=0/4). All chicken meat sample bought from traditional (n=4/4) are also contaminated by cefoxitin-sensitive Staphylococcus aureus. Half of chicken meat sample bought from modern market (n=2/4) are contaminated by cefoxitin-sensitive Staphylococcus aureus, while the other half (n=2/4) are contaminated by cefoxitin-resistant Staphylococcus aureus.Conclusion: Antibiotic resistance is found and all chicken meat samples have been highly contaminated with bacteria therefore food-processing should be done correctly.